2013
DOI: 10.1111/cyt.12078
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of asymptomatic metastatic lobular carcinoma of breast on conventional and liquid‐based cervical cytology samples from the same patient

Abstract: Fujiwara M. Cutaneous sclerosing perineurioma of the digit. Int J Dermatol 2006;45:1086-8. 5. Housini I, Dabbs DJ. Fine needle aspiration cytology of perineurioma: report of a case with histologic, immunohistochemical and ultrastructural studies. Acta Cytol 1990;34:420-4. 6. Akerman M, Domanski HA. The cytological features of soft tissue tumors in fine needle aspiration smears classified according to histotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…Among these features, single cell filing was mentioned in almost all reports, 3,4,9,10,16,18 but “cell‐in‐cell” arrangement was not described in any of the reported cases. Many cytology reports described distinctive signet ring cell or intracytoplasmic mucin vacuole, which was not seen in our case 3,4,6,7,9,10,16,18 …”
Section: Figurecontrasting
confidence: 47%
See 2 more Smart Citations
“…Among these features, single cell filing was mentioned in almost all reports, 3,4,9,10,16,18 but “cell‐in‐cell” arrangement was not described in any of the reported cases. Many cytology reports described distinctive signet ring cell or intracytoplasmic mucin vacuole, which was not seen in our case 3,4,6,7,9,10,16,18 …”
Section: Figurecontrasting
confidence: 47%
“…There are many case reports of metastatic breast cancer identified in the uterine cervix, 1‐18 but only a few focus on its cytologic features in liquid‐based Pap tests 6,9 . Most cytology reports are older and on conventional Pap smears 1,3,4,7,10,13,16,18 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Biscotti et al [14] illustrated a TP sample of a lobular carcinoma showing dyshesive cells with eccentric nuclei and well-preserved nuclear detail in a clean background. More recently, Crossley et al [25] reported the case of a patient with a lobular carcinoma of the breast metastatic to the cervix. After treatment with chemotherapy for her breast tumor, a cervical sample was obtained and was prepared by the SP method, displaying cells with high nuclear-cytoplasmic ratio, hyperchromasia and intracytoplasmic lumina that were consistent with a diagnosis of metastatic lobular carcinoma.…”
Section: ‘Selected' Breast Lesionsmentioning
confidence: 99%